INCOME TAX AND ZAKAT: A QUR'ANIC AND LEGAL PERSPECTIVE AND IT'S EFFECT ON STATE REVENUE - Neneng Hartati; Vinna Sri Yuniarti (Finansha: Journal of Sharia Financial Management, 2023)
This study aims to identify and describe the Qur'anic perspective on Income Tax and Zakat; know and describe the Perspective of Law Number 36 of 2008 concerning Income Tax; and know and describe the effect of tax on income and zakat on state revenue quantitatively. This research uses descriptive method with qualitative and quantitative approaches. This research was conducted at the Office of the Director General of Taxes Regional Office and National Amil Zakat Agency Bandung City and Sumedang Regency, with interview data collection techniques, and secondary data, namely data obtained from data processing from related agencies. The data analysis technique used is a qualitative approach with data triangulation and a quantitative approach with statistical analysis in the form of multiple regression. The results showed that first, based on the Qur'an, zakat is part of the fourth pillar of Islam. The relationship that occurs because of zakat is not only the relationship of Habluminallah but also the relationship of Habluminannash; second, the perspective of Law No. 36 of 2008 concerning Income Tax is part of the state tax, where the tax is used for the benefit of the state. Third, based on quantitative results obtained income tax and zakat funds affect state revenue with an influence contribution of 94.9% while the remaining 5.1% is influenced by other factors.